Resolving inconsistencies in tutor expertise research: does lack of structure cause students to seek tutor guidance? - Schmidt, H G (Academic medicine : journal of the Association of American Medical Colleges, 1994)
To investigate under what conditions tutors' subject-matter expertise influences student achievement. Data were analyzed from 1,800 University of Limburg Faculty of Health Sciences students who in 1989-90 participated in tutorial groups led by content-expert staff tutors, non-expert staff tutors, or student tutors. Each student participated in an average of 4.1 tutorial groups. Overall, 4,111 data records were available for analysis. The basic analyses were of (1) students' achievement scores as a function of tutors' levels of subject-matter expertise and students' prior knowledge; (2) students' achievement scores as a function of tutors' levels of subject-matter expertise and educational units' levels of structure; and (3) differences in achievement between students guided by tutors of different levels of expertise in either high- or low-structure units. Statistical methods included analyses of variance. The level of subject-matter expertise of tutors had a positive influence on student achievement. Similar results were found for the students' prior knowledge and the levels of structure of the units; the more prior knowledge students had, the better were their performances on the end-of-unit test; and the higher the level of structure of the unit, the better the achievement. More important, interactions were found between tutor expertise on the one hand and prior knowledge and unit structure on the other, tutor expertise being mainly important if the unit was poorly structured or students reported lack of prior knowledge. The results suggest that students need a minimum level of structure in order to profit from problem-based instruction. This structure can be internally provided through prior knowledge available for understanding the new subjects, or offered by the environment in the form of cues of what is relevant and what should be the focus of the activities. If prior knowledge falls short, or if the environment lacks structure, students will turn to their tutors for help and direction. Under those conditions, students who are guided by a subject-matter expert tutor may benefit more than students guided by a non-expert staff tutor or by a student tutor. These findings may explain the widely divergent results of tutor-expertise research.